STRUCTURAL CHANGES AND OXIDATION OF FERROAN PHLOGOPITE WITH INCREASING TEMPERATURE: IN SITU NEUTRON POWDER DIFFRACTION AND FOURIER TRANSFORM INFRARED SPECTROSCOPY - Chon Ch.; Lee Ch.; Song Yu.; Kim S.A. (My University, 2006)
The thermal response of the natural ferroan phlogopite-1M, K2(Mg4.46Fe0.83Al0. 34Ti0.22)(Si5.51Al2. 49)O20[OH3.59F0.41] from Quebec, Canada, was studied with an in situ neutron powder diffraction. The in situ temperature conditions were set up at −263, 25, 100°C and thereafter at a 100°C intervals up to 900°C. The crystal structure was refined by the Rietveld method (R p=2.35–2.78%, R wp=3.01–3.52%). The orientation of the O–H vector of the sample was determined by the refinement of the diffraction pattern. With increasing temperature, the angle of the OH bond to the (001) plane decreased from 87.3 to 72.5°. At room temperature, a = 5.13 Å, b = 9.20 Å, c = 10.21 Å, β = 100.06° and V(volume) = 491.69 Å3. The expansion rate of the unit cell dimensions varied discontinuously with a break at 500°C. The shape of the M-octahedron underwent some significant changes such as flattening at 500°C. At temperatures above 500°C, the octahedral thickness and mean distance was decreased, while the octahedral flattening angle increased. Those results were attributed to the Fe oxidation and dehydroxylation processes. The dehydroxylation mechanism of the ferroan phlogopite was studied by the Fourier transform infrared spectroscopy (FTIR) after heated at temperatures ranging from 25 to 800°C with an electric furnace in a vacuum. In the OH stretching region, the intensity of the OH band associated with Fe2+(N B-band) begun to decrease outstandingly at 500°C. The changes of the IR spectra confirmed that dehydroxylation was closely related to the oxidation in the vacuum of the ferrous iron in the M-octahedron. The decrease in the angle of the OH bond to the (001) plane, with increasing temperature, might be related to the imbalance of charge in the M-octahedra due to Fe oxidation.
Keywords: FERROAN PHLOGOPITE; NEUTRON POWDER DIFFRACTION; FTIR; OXIDATION; DEHYDROXYLATION